Polysiloxane, adhesive, method for producing polysiloxane, and method for producing adhesive

The polysiloxane adhesive with a catechol group and flexible dimethylsiloxane units addresses the lack of shear strength and impact resistance in existing adhesives, providing strong and durable bonding across diverse materials.

JP7618181B2Active Publication Date: 2025-01-21KAGOSHIMA UNIV +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023513055
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-04-09
Filing Date
2022-04-08
Publication Date
2025-01-21
Estimated Expiration
2042-04-08

AI Technical Summary

Technical Problem

Existing adhesives lack sufficient shear strength and impact resistance, and polysiloxanes suitable for adhesive applications are not effectively utilized in manufacturing methods.

Method used

A polysiloxane adhesive composed of an adhesive monomer unit with a catechol group bonded via a urea bond and a flexible dimethylsiloxane unit, with a flexible monomer unit content ranging from 47 to 95 mol%, and a production method involving copolymerization, catechol group introduction, and optional alkylsilyl group modification to enhance adhesion properties.

Benefits of technology

The polysiloxane adhesive achieves excellent shear strength and impact resistance, maintaining adhesion under various conditions and material combinations, including bonding different materials like aluminum, stainless steel, copper, and glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618181000001
    Figure 0007618181000001
  • Figure 0007618181000002
    Figure 0007618181000002
  • Figure 0007618181000003
    Figure 0007618181000003
Patent Text Reader

Abstract

Provided are: an adhesive capable of achieving bonding with excellent shear strength and impact resistance; a polysiloxane composition able to be used as a component contained in this adhesive; and methods for producing the adhesive and the polysiloxane composition. This polysiloxane composition is a copolymer of: an adhesive monomer unit A comprising an organosiloxane unit having a substituent group RA2 that includes a catechol group; and a flexible monomer unit B comprising an organosiloxane unit that does not include a catechol group.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polysiloxane hmm, Adhesives, polysiloxane N The present invention relates to a method of manufacturing an adhesive. [Background technology]

[0002] In recent years, proteins with adhesive properties secreted by marine organisms such as mussels have been attracting attention. It has been revealed that the catechol group contained in the protein contributes to the expression of adhesive properties. In addition, the application of catechol groups to adhesives has been studied (see Patent Document 1 below). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2005 / 056708 Summary of the Invention [Problem to be solved by the invention]

[0004] The object of the present invention is to provide an adhesive capable of realizing adhesion with excellent shear strength and impact resistance, and a polysiloxane that can be used as a component of the adhesive. And , the adhesive and polysiloxane N and a manufacturing method thereof. [Means for solving the problem]

[0005] The polysiloxane according to the first aspect of the present invention is an adhesive monomer unit comprising an organosiloxane unit having a substituent containing a catechol group; a flexible monomer unit comprising an organosiloxane unit not containing a catechol group; A polysiloxane which is a copolymer of both the adhesive monomeric unit and the flexible monomeric unit are D units; the adhesive monomer unit and the flexible monomer unit constitute a linear main chain, the substituent containing a catechol group contains a urea group, The catechol group is bonded to a silicon atom constituting the adhesive monomer unit via a urea bond containing the urea group. And, The flexible monomer unit is a dimethylsiloxane unit.

[0007] According to the first aspect of the present invention Polysiloxane N The flexible monomer unit may account for 47 mol % or more and 95 mol % or less.

[0008] The substituent containing a catechol group may contain a hydrocarbon group.

[0010] The polysiloxane according to the second aspect of the present invention is an adhesive monomer unit comprising an organosiloxane unit having a substituent that includes a modified catechol group having a silylated structure in which each hydrogen atom of two hydroxyl groups bonded to the ortho-position of a benzene ring is substituted with an alkylsilyl group; Catechol group The modified catechol group and a flexible monomer unit comprising an organosiloxane unit not containing A polysiloxane which is a copolymer of both the adhesive monomeric unit and the flexible monomeric unit are D units; the adhesive monomer unit and the flexible monomer unit constitute a linear main chain, the substituent containing a modified catechol group contains a urea group, The modified catechol group is bonded to a silicon atom constituting the adhesive monomer unit via a urea bond containing the urea group. The flexible monomer unit may account for 47 mol % or more and 95 mol % or less of the polysiloxane according to the second aspect of the present invention. The substituent containing the modified catechol group may contain a hydrocarbon group.

[0011] The present invention The third perspective The adhesive according to the present invention is The first or second aspect of Polysiloxane related to N Contains.

[0012] The present invention The fourth viewpoint The adhesive according to the present invention is The present invention as described above The first or second aspect of Polysiloxane related to Hmm The first polysiloxanes each have a different content ratio of the flexible monomer unit. And and the second polysiloxane hmm, Contains do.

[0013] The present invention The fourth viewpoint The adhesive according to the present invention is The present invention as described above The first or second aspect of Polysiloxane related to Hmm Rina a third polysiloxane comprising The content ratio of the flexible monomer unit is And and the second polysiloxane And Different tertiary polysiloxanes hmm, It may further contain:

[0014] A method for producing a polysiloxane according to a fifth aspect of the present invention comprises the steps of: a first siloxane unit having a substituent that includes a urea group; does not have a substituent containing a urea group, a precursor polysiloxane generating step for generating a precursor polysiloxane which is a copolymer of a first siloxane unit and a second siloxane unit having a substituent composed of a hydrocarbon group, wherein both the first siloxane unit and the second siloxane unit are D units, and the first siloxane unit and the second siloxane unit form a linear main chain; a catechol group introduction step of reacting the precursor polysiloxane with a catecholamine to introduce a catechol group having two hydroxy groups bonded to the ortho positions of a benzene ring into the first siloxane unit via a urea bond containing the urea group; Including fruit, The second siloxane unit is a dimethylsiloxane unit.

[0015] The precursor polysiloxane producing step comprises: a precursor first siloxane unit which is a precursor of the first siloxane unit and has a compound containing an ammonium group as a substituent; Does not have a compound containing an ammonium group as a substituent copolymerizing said second siloxane unit to form a linear copolymer; a urea group forming step of reacting the copolymer formed in the copolymerization step with a carbonyl compound to replace the compound containing an ammonium group in the first precursor siloxane unit with the compound containing a urea group; may include:

[0017] The present invention 6 The method for producing a polysiloxane according to the present invention comprises the steps of: a precursor polysiloxane generating step for generating a precursor polysiloxane which is a copolymer of a first siloxane unit having a substituent containing a urea group and a second siloxane unit having a substituent consisting of a hydrocarbon group and not having a substituent containing a urea group, wherein both the first siloxane unit and the second siloxane unit are D units, and the first siloxane unit and the second siloxane unit constitute a linear main chain; a catechol group introduction step of reacting the precursor polysiloxane with a catecholamine to introduce a catechol group having two hydroxy groups bonded to the ortho positions of a benzene ring into the first siloxane unit via a urea bond containing the urea group; an alkylsilyl group introduction step in which the polymer obtained in the catechol group introduction step is reacted with a silylating agent to substitute an alkylsilyl group for each hydrogen atom of the two hydroxy groups bonded to the ortho positions of the benzene ring; and , Includes .

[0018] The present invention 6 The method for producing a polysiloxane according to the present invention comprises the steps of: After the alkylsilyl group introduction step, an alkylsilyl group elimination step of replacing the alkylsilyl group with the hydrogen atom again to reform a structure in which two hydroxy groups are bonded to the ortho positions of the benzene ring; It may further include。

[0019] The present invention The seventh viewpoint The method for producing an adhesive according to the present invention comprises the steps of: The present invention as described above The fifth or sixth aspect of Polysiloxane related to N The first polysiloxanes are obtained by the above-mentioned production method, and each of them has a different content ratio of the second siloxane unit. And and the second polysiloxane N A preparation process to prepare; The first polysiloxane And and the second polysiloxane N A mixing step of mixing the ingredients; Includes.

[0020] In a method for producing an adhesive according to a seventh aspect of the present invention, In the preparation step, at least a third polysiloxane is further prepared in addition to the first polysiloxane and the second polysiloxane, The third polysiloxane is obtained by the method for producing a polysiloxane according to the fifth or sixth aspect of the present invention described above, and a content ratio of the second siloxane unit in the third polysiloxane is different from that of the first polysiloxane and the second polysiloxane, In the mixing step, in addition to the first polysiloxane and the second polysiloxane, at least the third polysiloxane may be further mixed. 。 Effect of the Invention

[0021] The present invention The third or fourth aspect of The adhesive according to the present invention contains a copolymer of an adhesive monomer unit and a flexible monomer unit, and therefore can realize adhesion with excellent shear strength and impact resistance. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 is a conceptual diagram showing a local chemical structure of a polysiloxane composition according to a first embodiment. [Diagram 2]FIG. 1 is a conceptual diagram showing the global structure of a polysiloxane composition according to a first embodiment. [Diagram 3] 1 is a flowchart showing a method for producing a polysiloxane composition according to a first embodiment. [Figure 4] FIG. 1 is a schematic diagram showing a copolymerization process according to Examples 1-4. [Diagram 5] FIG. 2 is a conceptual diagram showing a urea group forming step and a catechol group introducing step according to Examples 1-4. [Figure 6] 1 is a graph showing the Fourier transform infrared spectroscopy (FT-IR) spectrum of the polysiloxane composition according to Examples 1-4. [Figure 7] Graph showing proton nuclear magnetic resonance ( 1 H-NMR) spectra of the polysiloxane compositions according to Examples 1-4. [Figure 8] FIG. 1 is a conceptual diagram showing a procedure for producing an evaluation sample. [Figure 9A] FIG. 11 is a stress-strain curve of evaluation samples according to Example 4 and Comparative Example 4. [Figure 9B] 4 is a stress-strain curve of evaluation samples according to Example 3 and Comparative Example 3. [Figure 9C] 4 is a stress-strain curve of evaluation samples according to Example 2 and Comparative Example 2. [Figure 9D] 2 is a stress-strain curve of evaluation samples according to Example 1 and Comparative Example 1. [Figure 10] FIG. 1 is a stress-strain curve showing the results when the adhesive surface area of ​​the evaluation samples according to Examples 1-4 and commercially available Reference Examples 1-10 is reduced. [Figure 11A] FIG. 11 is a stress-strain curve of a sample for evaluating adhesion of a glass fiber reinforced epoxy resin according to Example 3. [Figure 11B] FIG. 11 is a stress-strain curve showing the case where the adhesive surface area of ​​the glass fiber reinforced epoxy resin adhesive evaluation sample according to Example 3 is reduced. [Figure 12] FIG. 11 is a stress-strain curve of an unoxidized copper adhesion evaluation sample and an oxidized copper adhesion evaluation sample according to Example 3. [Figure 13] FIG. 1 is a stress-strain diagram of adhesion evaluation samples according to Examples 1-4 and commercially available Reference Examples 1-2 after immersion in water for two days. [Figure 14A] Photographs showing the results of an impact resistance test of an evaluation sample according to Example 4. [Figure 14B] Photographs showing the results of an impact resistance test of an evaluation sample according to Example 1. [Figure 14C] Photographs showing the results of an impact resistance test of an evaluation sample according to Comparative Example 5. [Figure 15] 5 is a flowchart showing a method for producing a polysiloxane composition according to a second embodiment. [Figure 16] FIG. 1 is a conceptual diagram showing the structure of a silylating agent according to a second embodiment. [Figure 17] FIG. 2 is a conceptual diagram showing the global structure of a protected polysiloxane composition according to a second embodiment. [Figure 18] FIG. 1 is a conceptual diagram showing an alkylsilyl group introduction step according to Example 5. [Figure 19] Graph showing 1H-NMR spectrum of the protected polysiloxane composition of Example 5. [Figure 20] FIG. 1 is a schematic diagram showing an alkylsilyl group-eliminating process according to Example 5. [Figure 21] 10 is a flowchart showing a method for producing an adhesive according to a third embodiment. [Figure 22] 4 is a graph showing the FT-IR spectrum of the polysiloxane composition according to Example 6. [Figure 23] Graph showing 1H-NMR spectrum of the polysiloxane composition according to Example 6. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] below , No. The polysiloxane compositions according to the first to third embodiments will now be described.

[0024] [First embodiment] The chemical structures of the monomer units of the polysiloxane composition according to this embodiment are shown in Figure 1. The polysiloxane composition according to this embodiment is a copolymer of adhesive monomer unit A, which mainly contributes to adhesion, and flexible monomer unit B, which mainly contributes to flexibility.

[0025] 1 means that the arrangement of the adhesive monomer unit A and the flexible monomer unit B in the polysiloxane composition is disordered. That is, the polysiloxane composition according to this embodiment is a random copolymer of the adhesive monomer unit A and the flexible monomer unit B.

[0026] The adhesive monomer unit A has two substituents R on the silicon atom. A1 and R A2 The siloxane unit is a D unit, which is a unit having a substituent R A1 The other substituent R A2 contains a catechol group which contributes to adhesiveness. The molar ratio of the catechol group to the adhesive monomer unit A is 1:1.

[0027] The flexible monomer unit B is composed of an organosiloxane unit that does not contain a catechol group. Specifically, the flexible monomer unit B is composed of two substituents R B1 and R B2 is a D unit having the formula:

[0028] The above-mentioned substituent R A1 , R B1 , and R B2 The hydrocarbon group constituting the substituent R may be, for example, one having 10 or less carbon atoms, specifically, an alkyl group having 10 or less carbon atoms. The alkyl group is preferably a methyl group. A1 , R B1 , and R B2 The three may be the same. That is, for example, the substituent R A1 may be a methyl group and the flexible monomer unit B may be a dimethylsiloxane unit.

[0029] However, the substituent R A1 , R B1 , and R B2 One of them may be different from the remaining two, or all three may be different from each other.

[0030] 2 shows the global structure of the polysiloxane composition according to this embodiment. The polysiloxane composition according to this embodiment has a structure in which a plurality of catechol groups are bonded to a main chain as side chains. The catechol groups are repeatedly and discretely arranged in the longitudinal direction of the main chain.

[0031] Each catechol group is represented by the substituent R A2 The main chain is composed of a random arrangement of the portion other than the catechol group in the adhesive monomer unit A shown in Fig. 1 and the flexible monomer unit B. In this embodiment, since both the adhesive monomer unit A and the flexible monomer unit B are D units, the main chain is linear.

[0032] The flexible monomer unit B shown in FIG. B1 and R B2 Since it does not contain a catechol group, it prevents the bond density of the catechol group to the main chain shown in FIG. 2 from becoming excessive, thereby playing a role in making the main chain flexible.

[0033] The softening of the main chain means that when the polysiloxane composition according to this embodiment is used as a component of an adhesive, the shear strength and impact resistance of the adhesive can be improved. That is, the flexible monomer unit B plays a role in adding shear strength and impact resistance to the strong adhesiveness exhibited by the catechol group of the adhesive monomer unit A.

[0034] In order to impart excellent flexibility to the main chain without impairing the strong adhesiveness of the catechol group, it is preferable that the flexible monomer unit B accounts for 47 mol % or more and 95 mol % or less of 100 mol % of the polysiloxane composition, and the remainder is accounted for by the adhesive monomer unit A. Here, the molar ratio of the adhesive monomer unit A to the flexible monomer unit B is as follows: 1 It can be identified by the integral ratio of signals appearing in the H-NMR spectrum.

[0035] Next, a method for producing the polysiloxane composition according to this embodiment will be described.

[0036] First, a linear copolymer is formed from a first siloxane unit, which is a precursor of the adhesive monomer unit A, and a second siloxane unit, which is a flexible monomer unit B. Next, a catechol group is introduced into the first siloxane unit in the copolymer, thereby obtaining the polysiloxane composition according to this embodiment.

[0037] According to the research of the present inventors, the introduction of catechol groups is particularly efficient when carried out via a urea bond structure. In other words, in order to increase the introduction rate of catechol groups, it is desirable to use a urea bond structure. Hereinafter, a method for producing a polysiloxane composition in which catechol groups are introduced using a urea bond structure will be specifically described.

[0038] As shown in FIG. 3, first, a copolymer is formed of a precursor first siloxane unit having a compound containing an ammonium group as a substituent and a second siloxane unit having a substituent made of a hydrocarbon group (copolymerization step S1).

[0039] Here, the first precursor siloxane unit is a precursor of the adhesive monomer unit A shown in FIG. 1. In addition, the substituent having an ammonium group-containing compound in the first precursor siloxane unit is the substituent R A2 The second siloxane unit is the same as the flexible monomer unit B shown in FIG.

[0040] Next, the copolymer formed in the copolymerization step S1 is reacted with a carbonyl compound to replace the compound containing an ammonium group in the first precursor siloxane unit with a compound containing a urea group (urea group forming step S2). Note that in this specification, the urea group refers to a group represented by -NH-CO-N= or a group represented by -NH-CO-N<.

[0041] Hereinafter, the precursor first siloxane unit in which the compound containing an ammonium group is replaced with a compound containing a urea group is referred to as a first siloxane unit. Also, the polymer that has been subjected to this urea group forming step S2 is referred to as a precursor polysiloxane composition.

[0042] Next, the precursor polysiloxane composition is reacted with catecholamine to introduce catechol groups into the first siloxane unit via urea bonds containing the urea groups (catechol group introduction step S3). As described above, the introduction rate of catechol groups can be increased by introducing urea bonds.

[0043] As a result, the substituent R A2 However, the polysiloxane composition according to the present embodiment has a urea bond and a catechol group bonded to the urea bond. The obtained polysiloxane composition can be used as a component of an adhesive, specifically as a main component. Here, the term "main component" refers to a content of more than 50 wt%, and is used as a concept including 100 wt%.

[0044] An embodiment of the manufacturing method shown in FIG. 3 will be described below with reference to FIGS.

[0045] As shown in FIG. 4, a mixture of dimethoxydimethylsilane (DMDMS) (MW=120.22 g / mol, purity: 98%) and 3-aminopropyldimethoxymethylsilane (APDMMS) (MW=163.2 g / mol, purity: 97%) was used as the starting material. The starting material was added with a catalyst and stirred in 50 wt% ethanol at 60°C for 12 hours. The catalyst used was concentrated hydrochloric acid (MW=36.46 g / mol, purity: 35-37%) equivalent to APDMMS and 2 equivalents of water relative to the total moles of DMDMS and APDMMS. Next, the resulting mixed solution was transferred to a polypropylene disposable tray and heated at 50°C for about 5 hours in an open system to evaporate the solvent. Next, the resulting viscous solid product was heated in an oven at 100°C for 2 hours to obtain a copolymer (hereinafter referred to as PDMS / PS-NH3Cl).

[0046] In this case, four types of PDMS / PS-NH3Cl with different molar ratios of DMDMS:APDMMS mixture (hereinafter referred to as "feed ratio") were obtained. Specifically, the one with a feed ratio of 5:5 is Example 1, the one with a feed ratio of 6:4 is Example 2, the one with a feed ratio of 7:3 is Example 3, and the one with a feed ratio of 8:2 is Example 4.

[0047] The steps up to this point are an example of the copolymerization step S1 shown in Fig. 3. The dimethylsiloxane unit constituting PDMS / PS-NH3Cl shown in Fig. 4 is an example of the second siloxane unit described above. The siloxane unit constituting PDMS / PS-NH3Cl together with the dimethylsiloxane unit is an example of the first precursor siloxane unit described above, and NH3Cl constituting the substituent is an example of a compound containing an ammonium group.

[0048] The description will be continued with reference to Fig. 5. Next, a mixture of PDMS / PS-NH3Cl (5.0 mmol unit) dissolved in 5 mL of dehydrated DMSO (dimethyl sulfoxide), 1.2 equivalents of 1,1'-carbonyldiimidazole (MW = 162.15 g / mol, purity: 97%) relative to the ammonium group dissolved in 1.5 to 3 mL of dehydrated DMSO, and 1.2 equivalents of triethylamine (MW = 101.19 g / mol, purity: 99%) relative to the ammonium group dissolved in 1.5 to 3 mL of dehydrated DMSO was stirred at room temperature for 15 minutes to obtain a precursor polysiloxane composition.

[0049] This step is an example of the urea group forming step S2 shown in FIG. 3. The 1,1'-carbonyldiimidazole used in this step is an example of the carbonyl compound already described. The structure shown in FIG. 5 in which imidazole is linked to an amide bond is an example of a compound containing the urea group -NH-CO-N< already described. A siloxane unit having this compound as a substituent is an example of the first siloxane unit already described.

[0050] Next, a mixed solution of dopamine hydrochloride (MW=189.64g / mol, purity: 98%) with respect to 2 equivalents of ammonium group dissolved in 2.5-5mL of dehydrated DMSO and triethylamine (MW=101.19g / mol, purity: 99%) with respect to 2 equivalents of ammonium group dissolved in 2.5-5mL of dehydrated DMSO was added to the mixed solution containing the precursor polysiloxane composition, and stirred at 50°C for 2 hours. After that, the reaction solution was added to ethyl acetate (400-600mL), and the precipitated white solid was collected by suction filtration. Next, the collected crude product was washed with purified water (20-40mL), and the insoluble portion was collected by decantation to obtain a polysiloxane composition (hereinafter referred to as PDMS / PS-U-Ph(OH)2).

[0051] This step is an example of the catechol group introduction step S3 shown in Figure 3. The dopamine hydrochloride used in this step is an example of the catecholamine already described. The first siloxane unit that has undergone this step is an example of the adhesive monomer unit A shown in Figure 1. The second siloxane unit that has undergone this step is an example of the flexible monomer unit B shown in Figure 1.

[0052] According to this process, the adhesive monomer unit A is substituted with the substituent R A2 As shown in FIG. 5, has a catechol group linked to a urea bond. In addition, according to this process, the substituent R A2 As shown in Fig. 5, in addition to the urea bond structure and the catechol group, the compound has a hydrocarbon group having a structure in which carbon atoms are linked in a chain, specifically, a polyethylene group. More specifically, according to this process, the substituent R A2 has a trimethylene group (-CH2CH2CH2-) connecting the silicon atom of the adhesive monomer unit A and the urea bond structure, and an ethylene group (-CH2CH2-) connecting the urea bond structure and the catechol group.

[0053] In addition, the PDMS / PS-U-Ph(OH)2 obtained as described above becomes partially insoluble when dried and stored, so it was stored in the form of a solution dissolved in a solvent, specifically, as an ethanol solution. After concentrating this ethanol solution (40°C) using a rotary evaporator, it was poured into water and the precipitated solid was used as an adhesive.

[0054] Figure 6 shows the FT-IR spectrum of PDMS / PS-U-Ph(OH)2 according to Examples 1 to 4. As mentioned above, the DMDMS:APDMMS ratio in the copolymerization step S1 is different between Examples 1 to 4. In Figure 6, the ratio is shown in brackets <>.

[0055] As shown in FIG. 6, in all of Examples 1 to 4, the absorption peak due to the urea bond was observed at 1630 cm -1 Near and 1580cm -1 This indicates that the urea bond was properly formed in the above-mentioned catechol group introduction step S3.

[0056] In addition, the FT-IR spectrum shows absorption peaks derived from siloxane bonds, as well as peaks derived from silicon atoms in siloxane units and the substituent R shown in Figure 1. A1 , R B1 , and R B2 Absorption peaks due to bonds with methyl groups as cations were also confirmed.

[0057] FIG. 7 shows the structure of PDMS / PS-U-Ph(OH)2 according to Example 1-4. 1 The H-NMR spectrum is shown. 1 In the H-NMR spectrum, a signal h derived from an aromatic ring was observed, confirming the introduction of a catechol group into the adhesive monomer unit A.

[0058] Also, 1The molar ratio of flexible monomer unit B: adhesive monomer unit A in PDMS / PS-U-Ph(OH)2 (hereinafter referred to as structural unit ratio) was calculated from the integral ratio of the signal a of the methyl proton adjacent to the silicon atom in the H-NMR spectrum and the signal h derived from the aromatic ring. In FIG. 7, the calculated structural unit ratio is shown in parentheses (), and the previously described charge ratio is shown in parentheses <>. As shown in FIG. 7, in each of Examples 1-4, the structural unit ratio of flexible monomer unit B: adhesive monomer unit A was almost the same as the charge ratio.

[0059] The evaluation results when PDMS / PS-U-Ph(OH)2 according to Examples 1-4 was used as an adhesive will be described below.

[0060] First, an ethanol solution of PDMS / PS-U-Ph(OH)2 according to Example 1-4 was prepared, and the ethanol solution was poured into water to precipitate a paste. The paste was used as an adhesive and evaluated. Since the adhesive is made of PDMS / PS-U-Ph(OH)2, the adhesive will also be referred to as "PDMS / PS-U-Ph(OH)2" below.

[0061] The procedure for preparing the evaluation sample will be described with reference to Fig. 8. A paste of PDMS / PS-U-Ph(OH)2 was applied to each of a pair of aluminum plates. In Examples 1 and 2, the powder was applied, sandwiched between aluminum plates, and heated to form a paste.

[0062] Next, the areas of the pair of aluminum plates coated with PDMS / PS-U-Ph(OH)2 (hereinafter referred to as adhesive surfaces) were attached to each other, fixed with clips, and dried by heating at 150°C for 12 hours. The area of ​​the adhesive surface was 125 mm2. 2 In this manner, evaluation samples according to Examples 1-4 were obtained. For comparison, the above-mentioned PDMS / PS-NH3Cl, which is a precursor of PDMS / PS-U-Ph(OH)2, was used as an adhesive, and evaluation samples according to Comparative Examples were also obtained in the same manner.

[0063] Then, a tensile shear test was carried out on each evaluation sample at room temperature in which a pair of aluminum plates was pulled apart in a direction parallel to their adhesive surfaces, and a stress-strain curve was measured.

[0064] 9A, 9B, 9C, and 9D show stress-strain curves of the evaluation samples according to Examples 4, 3, 2, and 1, respectively. In all of Examples 1 to 4, the adhesive surfaces of the samples did not peel off even when pulled to 8.16 MPa, which was the maximum stress measurable by the tensile shear tester used, and strong adhesiveness was confirmed.

[0065] On the other hand, as shown in FIG. 9A, in the case of PDMS / PS-NH3Cl (Comparative Example 4) with a mixing ratio of 8:2, peeling of the adhesive surface was confirmed at 3.0 MPa. Also, as shown in FIG. 9B, in the case of PDMS / PS-NH3Cl (Comparative Example 3) with a mixing ratio of 7:3, peeling of the adhesive surface was confirmed at 5.9 MPa. Also, as shown in FIG. 9C, in the case of PDMS / PS-NH3Cl (Comparative Example 2) with a mixing ratio of 6:4, peeling of the adhesive surface was confirmed at 7.4 MPa. Also, as shown in FIG. 9D, in the case of PDMS / PS-NH3Cl (Comparative Example 1) with a mixing ratio of 5:5, peeling of the adhesive surface was confirmed at 6.8 MPa.

[0066] The main difference in chemical structure between PDMS / PS-U-Ph(OH)2 according to Examples 1-4 and PDMS / PS-NH3Cl according to Comparative Examples 1-4 is whether or not a catechol group is introduced. Therefore, the results shown in Figures 9A-9D confirm that the catechol group contributes to the development of strong adhesiveness. As described above, PDMS / PS-U-Ph(OH)2 according to Examples 1-4 can achieve adhesion with excellent shear strength.

[0067] Next, in order to confirm the shear stress at the time of peeling of the evaluation samples according to Examples 1-4, the area of ​​the adhesive surface of the evaluation samples was reduced and the stress-strain curve was measured again.

[0068] The results are shown in Fig. 10. The sample for evaluating the adhesion of the same material according to Example 1 had a bonding surface area of ​​40 mm 2 The sample for evaluating the adhesion of the same material according to Example 2 had a bonding surface area of ​​50 mm 2 The sample for evaluating the adhesion of the same material according to Example 3 had a bonding surface area of ​​31 mm 2 The sample for evaluating the adhesion of the same material according to Example 4 had a bonding surface area of ​​36 mm 2 When the specimen was placed in the test piece, the shear strength was 19.6 MPa.

[0069] FIG. 10 also shows a stress-strain curve of an evaluation sample prepared in the same manner using a commercially available adhesive as Commercial Reference Example 1-10. The commercially available reference example 1 uses a commercially available acrylic resin adhesive (two-liquid radical polymerization type) and has an adhesive surface area of ​​40 mm 2 The shear strength was 14.0 MPa. Commercial Reference Example 2 uses a commercially available epoxy adhesive containing micro iron powder (two-liquid addition reaction type), and the adhesive surface area is 48 mm 2 The shear strength was 13.4 MPa. In the commercially available Reference Example 3, a commercially available polyvinyl alcohol adhesive (aqueous solution drying solidification type) was used, and the adhesive surface area was 125 mm 2 The shear strength was 1.4 MPa. In the commercially available Reference Example 4, a commercially available polyvinyl acetate adhesive (water-dispersed, dried, solidified type) was used, and the adhesive surface area was 125 mm 2 The shear strength was 0.7 MPa. In the commercially available Reference Example 5, a commercially available cyanoacrylate adhesive (moisture curing type) was used, and the adhesive surface area was 125 mm 2 The shear strength was 1.6 MPa. Commercially available Reference Example 6 uses a commercially available cyanoacrylate adhesive (moisture curing type) and has a bonding surface area of ​​125 mm2 The shear strength was 3.1 MPa. In the commercially available Reference Example 7, a commercially available epoxy adhesive (two-liquid addition reaction type) was used, and the adhesive surface area was 125 mm 2 The shear strength was 3.9 MPa. Commercially available Reference Example 8 uses a commercially available cyanoacrylate adhesive (moisture curing type) and has a bonding surface area of ​​125 mm 2 The shear strength was 4.4 MPa. Commercially available Reference Example 9 uses a commercially available cyanoacrylate adhesive (moisture curing type) and has a bonding surface area of ​​125 mm 2 The shear strength was 4.3 MPa. Commercially available Reference Example 10 uses a commercially available vinyl acetate resin adhesive (hot melt type), and the adhesive surface area is 125 mm 2 The shear strength was 4.6 MPa.

[0070] As shown in FIG. 10, it was confirmed that the samples for evaluating adhesion to similar materials according to Examples 1-4 exhibited shear strength superior to that of the commercially available Reference Examples 1 and 2 at room temperature, and far superior to that of the commercially available Reference Examples 3-10.

[0071] Next, the applicability to adhesion of glass fiber reinforced epoxy resin was examined for the adhesive of Example 3 as a representative example. First, an evaluation sample (hereinafter referred to as a glass fiber reinforced epoxy resin adhesion evaluation sample) was prepared by bonding a pair of glass fiber reinforced epoxy resin plates together using the adhesive of Example 3 in the same manner as in the preparation procedure of the evaluation sample described above.

[0072] The adhesive surface area is 125 mm 2 Then, in the same manner as in Figure 9, a tensile shear test was conducted in which the glass fiber reinforced epoxy resin plate was pulled apart in a direction parallel to the adhesive surface, and the stress-strain curve was measured.

[0073] The results are shown in Figure 11A. Even when pulled to 8.16 MPa, the maximum stress measurable by the tensile shear tester used, the adhesive surface of the sample did not peel off, confirming that the adhesive of Example 3 is applicable to adhesion of glass fiber reinforced epoxy resin. It is believed that the strong adhesiveness was due to the presence of the PDMS component, which shows flexibility, the catechol group, which shows strong adhesiveness to the material surface, and the crosslinked structure between the catechol groups formed by heating and drying.

[0074] Next, in order to confirm the shear stress at the time of peeling of the glass fiber reinforced epoxy resin adhesive evaluation sample of Example 3, the area of ​​the adhesive surface was 53 mm 2 The stress was then reduced to 0.05 and the stress-strain curve was measured again.

[0075] The results are shown in Figure 11B. The stress when the adhesive surface with the glass fiber reinforced epoxy resin plate peeled off was 18.8 MPa, indicating strong adhesion. It is believed that the strong adhesion is due to hydrogen bonds between the hydroxyl groups on the glass fiber reinforced epoxy resin surface and the catechol groups.

[0076] Next, the applicability to copper bonding was examined for the adhesive of Example 3 as a representative example. First, an evaluation sample (hereinafter referred to as an unoxidized copper adhesion evaluation sample) was prepared by bonding a pair of copper plates whose surfaces were hardly oxidized, using the adhesive of Example 3 in the same manner as in the preparation procedure of the evaluation sample described above.

[0077] Similarly, an evaluation sample (hereinafter referred to as an oxidized copper adhesion evaluation sample) was prepared by bonding a pair of copper plates whose surfaces had been subjected to an oxidation treatment in the same manner as in the preparation procedure of the evaluation sample described above, using the adhesive of Example 3. The oxidation treatment was performed by heating the copper plates in air at 150°C for 12 hours.

[0078] The adhesive surface area of ​​both the unoxidized copper adhesive evaluation sample and the oxidized copper adhesive evaluation sample was 125 mm 2Then, in the same manner as in FIG. 9, a tensile shear test was carried out on each sample, and a stress-strain diagram was measured.

[0079] The results are shown in Figure 12. The unoxidized copper adhesiveness evaluation sample showed a sufficient shear strength of 6.2 MPa, confirming that the adhesive of Example 3 is applicable to bonding copper plates.

[0080] Furthermore, the oxidized copper adhesive evaluation sample showed a large shear strength of 8.1 MPa. This is presumably because the hydrogen bonds and coordinate bonds between the copper oxide on the surface and the catechol group contributed to the strong adhesiveness by oxidizing the copper plate. Although copper oxide was described here as an example, the adhesive according to this Example 1-4 is considered to be particularly suitable for bonding aluminum oxide and other metals with oxidized surfaces in general.

[0081] Next, the results of the evaluation of water resistance will be described. The water resistance was examined for the same evaluation samples as those used to measure the stress-strain curve shown in FIG. 9. Specifically, the evaluation samples according to Examples 1-4 and Commercial Reference Examples 1 and 2 were immersed in water for two days, the water was wiped off, and the stress-strain curve was immediately measured. Note that the area of ​​the adhesive surface of each evaluation sample was 125 mm2. 2 It was decided.

[0082] The evaluation results of water resistance are shown in Fig. 13. In all of Examples 1 to 4, even when pulled up to 8.16 MPa, which is the maximum stress measurable by the tensile shear tester used, peeling of the adhesive surface did not occur, and sufficient water resistance was confirmed.

[0083] On the other hand, in the case of Commercial Reference Example 2, peeling of the adhesive surface was confirmed at 6.5 MPa. When the adhesive of Commercial Reference Example 2 attached to the peeled surface was observed, it was slightly damp. In addition, in the case of Commercial Reference Example 1, peeling did not occur during the measurement, but the adhesive surface peeled off when it was left for a while under stress after the measurement was completed. The adhesive of Commercial Reference Example 1 attached to the peeled surface was softer than the material before immersion. Therefore, it is considered that the evaluation samples of Commercial Reference Examples 1 and 2 peeled off due to the influence of water.

[0084] Next, the results of an impact resistance test performed on the same evaluation sample as that used in measuring the stress-strain curve shown in FIG. 9 will be described.

[0085] 14A shows the pattern of the impact resistance test for the evaluation sample according to Example 4. As shown in the figure, the impact resistance test was performed by hitting the evaluation sample with a hammer from a direction perpendicular to the adhesive surface. The adhesive surface of the evaluation sample according to Example 4 did not peel off even when it was hit with a hammer, and deformation of the aluminum plate was confirmed. Furthermore, even when the deformed aluminum plate was hit again with a hammer, peeling of the adhesive surface was not confirmed.

[0086] Although not shown, the evaluation samples according to Examples 2 and 3 also gave results similar to those of Example 4.

[0087] 14B shows the pattern of the impact resistance test for the evaluation sample according to Example 1. The adhesive surface of the evaluation sample according to Example 1 did not peel off even after being hit once with a hammer, and it showed excellent impact resistance similar to that of Example 4. As described above, PDMS / PS-U-Ph(OH)2 according to Examples 1-4 can realize adhesion with excellent impact resistance.

[0088] However, when the evaluation sample of Example 1 was struck again with a hammer, the adhesive surface peeled off as shown in Fig. 14B. That is, Example 1 exhibits excellent impact resistance, but is inferior in impact resistance to Example 4. The difference between Example 1 and Example 4 lies in the proportion of flexible monomer unit B in PDMS / PS-U-Ph(OH)2.

[0089] Therefore, in order to clarify the role of the flexible monomer unit B in PDMS / PS-U-Ph(OH)2, a polysiloxane composition consisting of a polymer of only the adhesive monomer unit A out of the adhesive monomer unit A and the flexible monomer unit B was prepared as Comparative Example 5. For the adhesive monomer unit A, a siloxane unit having a structure in which a catechol group is bonded to methylsiloxane via a urea bond, as shown in Figure 5, was used.

[0090] Then, this polysiloxane composition according to Comparative Example 5 (hereinafter referred to as PS-U-Ph(OH)2) was used as an adhesive to obtain an evaluation sample according to Comparative Example 5 in the same manner.

[0091] 14C shows the pattern of the impact resistance test for the evaluation sample according to Comparative Example 5. When the evaluation sample according to Comparative Example 5 was lightly hit once with a hammer, the adhesive surface was easily peeled off. In other words, the evaluation sample according to Comparative Example 5 did not exhibit sufficient impact resistance.

[0092] 14A-14C, it can be seen that the lower the proportion of flexible polymer unit B in PDMS / PS-U-Ph(OH)2, the lower the impact resistance of the bond. Conversely, it has become clear that the flexible polymer unit B contributes to improving the impact resistance of the bond.

[0093] From the above test results, it can be said that in order to obtain particularly excellent impact resistance, the content of flexible polymer unit B in PDMS / PS-U-Ph(OH)2 is preferably 47 mol% or more, more preferably 58 mol% or more, even more preferably 66 mol% or more, and even more preferably 75 mol% or more.

[0094] On the other hand, in order to ensure a sufficient amount of adhesive monomer unit A, which contributes to strong shear strength, in PDMS / PS-U-Ph(OH)2, the content of flexible polymer unit B is preferably 95 mol% or less, more preferably 90 mol% or less, more preferably 85 mol% or less, and even more preferably 80 mol% or less.

[0095] Next, the results of a heat resistance test performed on the same evaluation sample as that used in measuring the stress-strain curve shown in FIG. 9 will be described.

[0096] Each of the adhesion evaluation samples according to Examples 1 to 4 was heated in an oven with a 5 kg weight hanging from it. The heating temperature was gradually increased. During heating, the load of the weight acts as a shear force on the adhesive surfaces of the pair of aluminum plates.

[0097] As a result, in all of Examples 1 to 4, the bonded state between the pair of aluminum plates was maintained even when the temperature reached 180° C. That is, the adhesion evaluation samples according to Examples 1 to 4 exhibited heat resistance at 180° C. This is presumably because the crosslinking reaction between catechol groups proceeded due to the heating and drying, forming a network structure, which adequately suppressed softening even at relatively high temperatures.

[0098] Next, in order to examine the heat resistance when used to bond dissimilar materials, an evaluation sample (hereinafter referred to as an aluminum-stainless steel adhesion evaluation sample) was prepared by bonding a pair of aluminum plates and stainless steel plates together in a manner similar to that used to prepare the evaluation sample described above.

[0099] Then, with a weight of 5 kg suspended from each of the aluminum-stainless steel adhesion evaluation samples according to Examples 1-4, each evaluation sample was heated in an oven. The heating temperature was gradually increased to 150°C. As a result, the adhesion state of the aluminum-stainless steel adhesion evaluation samples according to Examples 1-4 was maintained. Furthermore, even when the samples were cooled to room temperature, the adhesive surface did not peel off, and it was confirmed that the adhesiveness could be maintained even when the temperature changed from room temperature to 150°C.

[0100] This is presumably because the formation of a cross-linked structure between the catechol components suppresses softening at high temperatures, while the flexibility of the PDMS component is able to alleviate thermal distortion caused by differences in the thermal expansion coefficients of the different materials.

[0101] Next, the applicability of the adhesive according to Example 1-4 to adhesion between aluminum and glass was examined. Using the adhesive according to Example 1-4, an evaluation sample (hereinafter referred to as an aluminum-glass adhesion evaluation sample) was prepared by bonding a pair of aluminum plates and a glass plate in the same manner as the above-mentioned preparation procedure of the evaluation sample.

[0102] In this case, in all of the aluminum-glass adhesion evaluation samples, the aluminum plate and the glass plate were bonded with sufficient strength, confirming that the adhesives of Examples 1-4 were applicable to bonding aluminum and glass.

[0103] Furthermore, the aluminum-glass adhesion evaluation samples according to Examples 1-4 were heated and dried, then cooled to room temperature, and the adhesion state at that time was observed. As a result, it was confirmed that there was no peeling of the adhesive surface or damage to the glass plate. From this, it was found that the adhesive according to Examples 1-4 has a flexible structure that can relieve thermal distortion caused by the difference in thermal expansion coefficients caused by temperature changes between different materials.

[0104] [Second embodiment] In the adhesive having the structure shown in FIG. 2, hydrogen bonds can be formed between the hydroxyl group of a catechol group and the hydroxyl group of another catechol group. In this way, chemical bonding between the catechol groups constituting the adhesive reduces the viscosity of the adhesive, and thus shortens the shelf life of the adhesive. Therefore, an adhesive that can be stably stored for a long period of time is desired. A second embodiment that further solves this problem will be described below.

[0105] Figure 15 shows the procedure of the method for producing a polysiloxane composition according to this embodiment. The copolymerization step S1, the urea group formation step S2, and the catechol group introduction step S3 are the same as those in the first embodiment, so duplicated explanations will be omitted. The catechol group introduced in the catechol group introduction step S3 (hereinafter, referred to as an unprotected catechol group) has a structure in which two hydroxy groups are bonded to the ortho positions of a benzene ring, as shown in Figures 2 and 5.

[0106] In this embodiment, after the catechol group introducing step S3, the polymer obtained in the catechol group introducing step S3 (hereinafter referred to as an unprotected polysiloxane composition) is reacted with a silylating agent (alkylsilyl group introducing step S4).

[0107] As shown in FIG. 16, the silylating agent has three alkyl groups R attached to the silicon atom. C1 , R C2 , and R C3 A trialkylsilicon compound having a structure in which an alkyl group R is bonded to an arbitrary substituent X can be used. C1 , R C2 , R C3 may be identical to one another, may be different from one another, or one may be different from the other two.

[0108] Examples of trialkylsilicon compounds include trialkylalkoxysilanes in which the substituent X is an alkoxy group, trialkylhalogenosilanes in which the substituent X is a halogeno group, and silazanes which are other trialkylsilicon compounds in which the substituent X contains a nitrogen-silicon bond. Examples of trialkylhalogenosilanes include trialkylchlorosilanes in which the substituent X is a chloro group.

[0109] In the alkylsilyl group introduction step S4 shown in FIG. 15, the unprotected polysiloxane composition is reacted with the silylating agent to replace the hydrogen atoms of the two hydroxy groups bonded to the ortho positions of the benzene ring in the unprotected catechol group with alkylsilyl groups.

[0110] The global structure of the polysiloxane composition obtained through the alkylsilyl group introduction step S4 (hereinafter referred to as the protected polysiloxane composition) is shown in Figure 17. The protected polysiloxane composition has a silylated structure in which each hydrogen atom of the hydroxy group in the unprotected catechol group shown in Figure 2 is substituted with an alkylsilyl group R.

[0111] Hereinafter, such a catechol group in which the hydrogen atom of an unprotected catechol group has been substituted with an alkylsilyl group will be specifically referred to as a "modified catechol group".

[0112] The alkylsilyl group R acts as a protecting group that inhibits chemical bonding between the modified catechol groups, and therefore the protected polysiloxane composition obtained through the alkylsilyl group introduction step S4 is less susceptible to changes over time, such as a gradual increase in viscosity, and can be stored stably for a long period of time.

[0113] The protected polysiloxane composition may be used as a main component of an adhesive, similar to the unprotected polysiloxane composition, provided that the alkylsilyl group R as the above-mentioned protecting group may be removed when the composition is used as an adhesive.

[0114] Returning to Fig. 15, the description will be continued. In this embodiment, after the alkylsilyl group introduction step S4, the alkylsilyl group R as a protecting group is removed. That is, the alkylsilyl group R as a protecting group is replaced by a hydrogen atom again (alkylsilyl group removal step S5). This forms a structure in which two hydroxy groups are bonded to the ortho positions of the benzene ring. That is, the modified catechol group is returned to an unprotected catechol group.

[0115] The method of replacing the protecting group with a hydrogen atom is arbitrary. As an example, the protecting group can be replaced with a hydrogen atom by hydrolyzing the protected polysiloxane composition under acidic conditions. As another example, the protecting group can be replaced with a hydrogen atom by heating the protected polysiloxane composition.

[0116] An embodiment of the manufacturing method shown in FIG. 15 will now be described with reference to FIGS.

[0117] As shown in Fig. 18, PDMS / PS-U-Ph(OH)2 according to Example 3 was prepared in the manner described above, and reacted with hexamethyldisilazane (HMDS). Specifically, 4.64 mmol (0.7485 g) of HMDS was added to 0.72 mmol unit (0.1048 g) of PDMS / PS-U-Ph(OH)2 according to Example 3. The amount of HMDS added was adjusted to 20 equivalents relative to the adhesive monomer unit A in PDMS / PS-U-Ph(OH)2 according to Example 3.

[0118] Next, the PDMS / PS-U-Ph(OH)2 and HMDS were stirred with a spatula for about 20 minutes, and further stirred with a stirrer at room temperature for 1 hour. The stirred mixture was then poured into about 60 mL of hexane, and the precipitate was obtained by decantation. This precipitate is the protected polysiloxane composition of Example 5.

[0119] The steps up to this point are an example of the alkylsilyl group introduction step S4 shown in FIG. 15. PDMS / PS-U-Ph(OH)2 according to Example 3 is an example of the unprotected polysiloxane composition described above. HMDS is an example of the silylating agent shown in FIG. 16. HMDS is an alkyl group R C1 , R C2 , R C3 16. The compound has a methyl group as the substituent X and a trimethylsilicon compound containing a nitrogen-silicon bond as the substituent X shown in FIG.

[0120] As shown in Fig. 18, the protected polysiloxane composition according to Example 5 obtained as a precipitate has a modified catechol group. The modified catechol group has a silylated structure in which the hydrogen atoms of the two hydroxyl groups bonded to the ortho positions of the benzene ring in the unprotected catechol group are substituted with trimethylsilyl groups, which are an example of the alkylsilyl group R described above. In Fig. 18, the protected polysiloxane composition according to Example 5 is represented as PDMS / PS-Ph[OSi(CH3)3]2.

[0121] As described above, it was found that the solubility in a solvent was improved by substituting the hydrogen atom of the hydroxy group in the unprotected catechol group with an alkylsilyl group R. Specifically, the protected polysiloxane composition according to Example 5 was dissolved in any of dimethylformamide, methanol, ethanol, acetone, ethyl acetate, chloroform, diethyl ether, and toluene, while the unprotected polysiloxane composition according to Example 3 was dissolved only in dimethylformamide, methanol, and ethanol among these solvents.

[0122] However, the protected polysiloxane composition of Example 5 was difficult to dissolve in dimethyl sulfoxide, whereas the unprotected polysiloxane composition of Example 3 was dissolved in dimethyl sulfoxide.

[0123] FIG. 19 shows the results of the protected polysiloxane composition of Example 5. 1 The H-NMR spectrum is shown in Figure 19. 1In the H-NMR spectrum, a signal j derived from the methyl proton of the trimethylsilyl group as the alkylsilyl group R is observed. 1 In the H-NMR spectrum, a signal i derived from the hydroxy group of the unprotected catechol group was observed. The signal i is shown in FIG. 1 This is not confirmed by the H-NMR spectrum. The above facts support the fact that the hydrogen atom of the hydroxyl group in the unprotected catechol group has indeed been replaced by a trimethylsilyl group.

[0124] In the adhesive monomer unit A, the silicon atom and the urea bond structure are connected by a skeleton consisting of multiple carbon atoms. The introduction rate of the trimethylsilyl group as the alkylsilyl group R was calculated to be 99% by using the integral value of the signal b derived from the carbon atoms that are directly bonded to the silicon atom among the carbon atoms that constitute the skeleton and the integral value of the above-mentioned signal j.

[0125] This means that 99% of the hydroxy groups present in the unprotected catechol group were replaced with trimethylsilyl groups. 1 The fact that no signal i derived from a hydroxy group was observed in the H-NMR spectrum indicates that no unprotected catechol group was present in the protected polysiloxane composition of Example 5, and therefore it is believed that a substantially 100% introduction rate was achieved.

[0126] The description will be continued with reference to Fig. 20. Next, in the hope of improving the adhesive strength when used as an adhesive, the trimethylsilyl group as a protecting group was removed from the protected polysiloxane composition of Example 5. This step is an example of the alkylsilyl group removal step S5 shown in Fig. 15.

[0127] Specifically, an acid was generated by adding and mixing a solution of 1.7 mg of an acid anhydride, specifically a solution of 3,3',4,4'-benzophenonetetracarboxylic dianhydride dissolved in 1 mL of acetone to a solution of 57.0 mg of the protected polysiloxane composition of Example 5 dissolved in 1 mL of acetone. The amount of the acid anhydride added was 3 wt% based on 100 wt% of the protected polysiloxane composition of Example 5.

[0128] Under the acidic conditions in which the acid is thus generated, hydrolysis occurs, and the trimethylsilyl groups in the protected polysiloxane composition of Example 5 are replaced with hydrogen atoms by the hydrolysis, thus reforming a structure in which two hydroxy groups are bonded to the ortho positions of the benzene ring.

[0129] Hereinafter, the composition in which the modified catechol group in the protected polysiloxane composition is returned to the unprotected catechol group in this manner will be referred to as a “deprotected polysiloxane composition.” The deprotected polysiloxane composition of Example 5 can be obtained by evaporating the acetone used as the solvent described above.

[0130] The results of evaluation of the adhesive properties of the protected polysiloxane composition and the deprotected polysiloxane composition of Example 5 are described below.

[0131] An evaluation sample was prepared by bonding a pair of aluminum plates with the protected polysiloxane composition of Example 5 in the manner described with reference to FIG. 2 Thus, it was found that the protected polysiloxane composition of Example 5 can be used as an adhesive without necessarily having to contain an acid anhydride.

[0132] On the other hand, an evaluation sample was prepared in the same manner as in Example 5, consisting of a pair of aluminum plates bonded together with the deprotected polysiloxane composition of Example 5. A tensile shear test was then carried out on the evaluation sample, revealing that the area of ​​the bonded surface was 61 mm 2 Even when the shear strength was reduced to 10.9 MPa, it still showed sufficient shear strength. This result confirmed that the adhesive strength can be improved by promoting the removal of the protecting group by adding an acid anhydride when used as an adhesive.

[0133] In the above-described Example 5, the removal of the protecting group was promoted by coexisting the protected polysiloxane composition with an acid anhydride, but the method for removing the protecting group is arbitrary, as described with reference to Fig. 15. Modified examples of the method for removing the protecting group will be described below.

[0134] In order to confirm that the protecting group can be removed by heating without using an acid anhydride, the protected polysiloxane composition according to Example 5 was dissolved in dimethylformamide as a solvent and stirred for 1 hour while being heated to 150° C., which is the same temperature as during adhesion. The solvent was then removed to obtain a deprotected polysiloxane composition according to the modified example.

[0135] And the deprotected polysiloxane composition according to the modified example 1 The H-NMR spectrum was measured, and the results shown in FIG. 1 Compared with the H-NMR spectrum, a decrease in the area of ​​signal j derived from the methyl proton of the trimethylsilyl group as the alkylsilyl group R and an increase in the area of ​​signal i derived from the hydroxyl group of the unprotected catechol group were observed. In other words, it was confirmed that the modified catechol group can be restored to the unprotected catechol group by heating at 150°C without using an acid anhydride.

[0136] [Third embodiment] Next, we will discuss the viscosity, which is an index of the ease with which an adhesive can be applied to an object.

[0137] As described with reference to Figures 9A-9D, catechol groups contribute to the development of adhesiveness. Therefore, in terms of increasing the adhesive strength of the adhesive, it can be said that a higher content of adhesive monomer unit A is advantageous. Meanwhile, according to research by the inventors of the present application, the viscosity of the adhesive at room temperature decreases as the content of flexible monomer unit B increases. Therefore, in terms of improving the ease of application to an object, a higher content of flexible monomer unit B is advantageous.

[0138] Therefore, in practical use, it is desirable to achieve a balance between obtaining sufficient adhesive strength and improving ease of application. In order to achieve this balance, it would be convenient if the content ratio of the flexible monomer unit B in the adhesive could be easily adjusted depending on the application of the adhesive. Hereinafter, an embodiment for achieving this will be described.

[0139] 21, in this embodiment, first, a plurality of polysiloxane compositions having different structural unit ratios as described above are prepared (preparation step S11). Then, the plurality of polysiloxane compositions are mixed to obtain an adhesive as a mixture of the plurality of polysiloxane compositions (mixing step S12).

[0140] According to this method, among the multiple types of polysiloxane compositions prepared in the preparation step S11, the one with a relatively high content of flexible monomer units B plays the role of a thinner. Specifically, when the first polysiloxane composition is mixed with the second polysiloxane composition with a lower content of flexible monomer units B than the first polysiloxane composition in the mixing step S12, the first polysiloxane composition plays the role of a thinner that reduces the viscosity of the second polysiloxane composition. Therefore, the viscosity of the resulting adhesive can be easily adjusted by the mixing ratio of the first polysiloxane composition and the second polysiloxane composition.

[0141] A specific example of the manufacturing method shown in FIG. 21 will be described below.

[0142] First, as the first polysiloxane composition serving as the thinner described above, PDMS / PS-U-Ph(OH)2 of Example 6 was prepared in the same manner as in Examples 1-4, except that the DMDMS:APDMMS ratio described above was set to 19:1.

[0143] However, in the copolymerization step S1 in Example 6, when the mixed solution containing DMDMS, APDMMS, a catalyst, and a solvent was heated to evaporate the solvent from the mixed solution, the liquid surface area of ​​the mixed solution was made smaller than that in Examples 1 to 4. This was to suppress the volatilization of the cyclic oligomer that contributes to the formation of the flexible monomer unit B.

[0144] 22 shows the FT-IR spectrum of PDMS / PS-U-Ph(OH)2 according to Example 6. In Example 6, too, an absorption peak due to a urea bond was observed at a wavenumber of 1632 cm -1 and wave number 1575 cm -1 This confirmed that the urea bond was properly formed in the above-mentioned catechol group introduction step S3.

[0145] FIG. 23 shows the structure of PDMS / PS-U-Ph(OH)2 according to Example 6. 1 The H-NMR spectrum is shown. 1 In the H-NMR spectrum, a signal h derived from an aromatic ring was observed. This confirmed the introduction of a catechol group into the adhesive monomer unit A. 1 From the integral ratio of the signal a of the methyl proton adjacent to the silicon atom in the H-NMR spectrum to the signal h derived from the aromatic ring, the structural unit ratio, which is the molar ratio of flexible monomer unit B:adhesive monomer unit A in PDMS / PS-U-Ph(OH)2, was calculated to be 93:7. In Figure 23, the structural unit ratio is shown in parentheses (), and the aforementioned charge ratio is shown in parentheses <>.

[0146] On the other hand, as the second polysiloxane composition described above, PDMS / PS-U-Ph(OH)2 according to the above-mentioned Example 3 was prepared. Then, PDMS / PS-U-Ph(OH)2 according to Example 6 as the first polysiloxane composition and PDMS / PS-U-Ph(OH)2 according to Example 3 as the second polysiloxane composition were mixed under conditions where the mass ratio of the first polysiloxane composition:second polysiloxane composition was 1:3 to obtain an adhesive according to the example.

[0147] Specifically, first, PDMS / PS-U-Ph(OH)2 according to Example 6 and PDMS / PS-U-Ph(OH)2 according to Example 3, each of which was weighed out to have a mass ratio of 1:3, were dissolved in ethanol and mixed to prepare a mixed solution. Next, the mixed solution was concentrated using a rotary evaporator, and then poured into water while stirring to precipitate the adhesive according to the example.

[0148] The results of evaluation of the adhesive properties of the adhesive according to this example will be described below.

[0149] An evaluation sample was prepared by bonding a pair of aluminum plates with the adhesive of this embodiment in the manner described with reference to Fig. 8. A tensile shear test was then carried out on the evaluation sample, and as in the case of Examples 1-4, the adhesive surfaces of the evaluation sample did not peel off even when pulled up to 8.16 MPa, which was the maximum stress measurable by the tensile shear tester used, confirming strong adhesion. In order to confirm the shear stress at which the adhesive surfaces peel off, the adhesive surface area was reduced to 61 mm2. 2 When the test piece was placed in this position, it showed sufficient shear strength of 9.6 MPa.

[0150] In addition, the evaluation sample was subjected to an impact resistance test in the manner described with reference to Figures 14A and 14B. It was confirmed that the adhesive surface of the evaluation sample did not peel off even when hit with a hammer, and the evaluation sample exhibited excellent impact resistance.

[0151] The same evaluation sample was also subjected to the heat resistance test described above. The sample maintained its adhesion even at 250°C when a 5kg weight was applied to the adhesive surface as a shear force. In other words, heat resistance up to 250°C was confirmed.

[0152] The adhesive of this example was used to prepare a sample for evaluating the adhesion between aluminum and stainless steel, as described above. As in Example 1-4, the sample for evaluating the adhesion between aluminum and stainless steel maintained its adhesive state even when heated to 150° C. with a load of 5 kg acting as a shear force on the adhesive surface, and also maintained its adhesive state when cooled to room temperature.

[0153] Next, the results of an evaluation of the ease of application of the adhesive according to this embodiment will be described.

[0154] The PDMS / PS-U-Ph(OH)2 of Example 3 as the second polysiloxane composition described above was in a hard paste state. On the other hand, the PDMS / PS-U-Ph(OH)2 of Example 6 as the first polysiloxane composition was in a liquid state. And the adhesive of this example, which was a mixture of the two, was in a soft paste state.

[0155] It was confirmed that the ease of application of the adhesive according to this example to a plate-shaped object was certainly improved compared to the PDMS / PS-U-Ph(OH)2 according to Example 3 as the second polysiloxane composition. This is because the first polysiloxane composition played the role of a thinner that reduces the viscosity of the second polysiloxane composition.

[0156] The mass ratio of the first polysiloxane composition:second polysiloxane composition described above, 1:3, is converted to a molar ratio of monomer units of 34:66. Therefore, the molar ratio of flexible monomer unit B:adhesive monomer unit A in the adhesive according to this example is (93×34+66×66):(7×34+34×66)≈75:25.

[0157] This molar ratio value is close to the structural unit ratio of 75:25 of PDMS / PS-U-Ph(OH)2 according to Example 4. However, it was confirmed that the adhesive according to this example is easier to apply at room temperature than the PDMS / PS-U-Ph(OH)2 according to Example 4.

[0158] In other words, it was found that when the molar ratio of flexible monomer unit B:adhesive monomer unit A is the same, an adhesive made by mixing multiple types of polysiloxane compositions each having a different structural unit ratio can be easier to apply than an adhesive made of a single type of polysiloxane composition.

[0159] The above describes an example in which the content ratio of the flexible monomer unit B in the adhesive as a mixture is 75 mol%. The content ratio of the flexible monomer unit B is not limited to this value, and can be arbitrarily adjusted by the mixing ratio of the first polysiloxane composition and the second polysiloxane composition. In order to achieve a balance between obtaining sufficient adhesive strength and improving ease of application, the content ratio of the flexible monomer unit B in the adhesive as a mixture is preferably 47 mol% or more and 95 mol% or less.

[0160] In the above examples, a manufacturing method in which the first polysiloxane composition and the second polysiloxane composition are mixed is exemplified. However, in addition to the first polysiloxane composition and the second polysiloxane composition, a third polysiloxane composition having a structural unit ratio different from those of the first polysiloxane composition and the second polysiloxane composition may be further mixed, or four or more types of polysiloxane compositions having structural unit ratios different from each other may be mixed.

[0161] In this way, when mixing a plurality of polysiloxane compositions having different structural unit ratios, at least one of the plurality of polysiloxane compositions may be the deprotected polysiloxane composition described above. As described above, a protected polysiloxane composition can also be used as an adhesive, so at least one of the plurality of polysiloxane compositions described above may be a protected polysiloxane composition in which an unprotected catechol group is replaced with a modified catechol group.

[0162] The adhesive according to the comparative example will be described below.

[0163] In the above-mentioned examples, when obtaining an adhesive as a mixture, a first polysiloxane composition in which the content ratio of adhesive monomer unit A is suppressed to 7 mol% in order to reduce the viscosity was used as a thinner. Also, as described above, it is recognized that the lower the content ratio of adhesive monomer unit A, the lower the viscosity of the obtained polysiloxane composition tends to be.

[0164] Therefore, in order to investigate whether a polysiloxane in which the content of adhesive monomer unit A was reduced to 0 mol% could function as the thinner described above, an attempt was made to prepare an adhesive using silicone oil that does not contain catechol groups as the thinner.

[0165] Specifically, silicone oil and PDMS / PS-U-Ph(OH)2 according to Example 3 as the second polysiloxane composition described above were mixed under the condition that the mass ratio of silicone oil to second polysiloxane composition was 1:3, and the mixture was dissolved in ethanol and poured into water. As a result, silicone oil and PDMS / PS-U-Ph(OH)2 were not compatible with each other, and the two precipitated in a separated state. In other words, silicone oil that does not contain a catechol group could not act as a thinner for PDMS / PS-U-Ph(OH)2.

[0166] These results show that in order for the first polysiloxane composition to be compatible with the second polysiloxane composition and thus act as a thinner for the second polysiloxane composition, the first polysiloxane composition needs to contain even a small amount of adhesive monomer unit A.

[0167] As an example, a polysiloxane composition having a content of adhesive monomer units A of more than 0 mol % and not more than 10 mol % can be used as a thinner for another polysiloxane composition having a content of adhesive monomer units A of more than 10 mol %.

[0168] Various modifications of the present invention are possible without departing from the broad spirit and scope of the present invention. The above-mentioned embodiments and examples are for the purpose of explaining the present invention and do not limit the scope of the present invention. The scope of the present invention is indicated by the claims, not by the embodiments and examples. Various modifications made within the scope of the claims and within the scope of the meaning of the invention equivalent thereto are considered to be within the scope of the present invention.

[0169] This application is based on Japanese Patent Application No. 2021-66515 filed in Japan on April 9, 2021. The entire specification, claims, and drawings of Japanese Patent Application No. 2021-66515 are incorporated herein by reference. [Industrial Applicability]

[0170] The adhesive according to the present disclosure can be used, for example, for bonding locations where shear strength and impact resistance are required. As a specific example, the adhesive according to the present disclosure can be used for bonding components that constitute an automobile. Since the cured product of the adhesive according to the present disclosure has shear strength and impact resistance, it can stably maintain a strong bonded structure even when subjected to an impact load associated with vibration or collision while the automobile is running.

[0171] The adhesive according to the present disclosure can also be used to bond different materials together. This makes it possible to realize a multi-material structure in which different materials are arranged in the right places. In particular, the adhesive is suitable for bonding any two materials selected from the group consisting of aluminum, stainless steel, copper, glass, and epoxy resin. The multi-material structure contributes to reducing the weight of transportation vehicles such as automobiles and aircraft.

Claims

1. an adhesive monomer unit comprising an organosiloxane unit having a substituent containing a catechol group; a flexible monomer unit comprising an organosiloxane unit not containing a catechol group; A polysiloxane which is a copolymer of both the adhesive monomer unit and the flexible monomer unit are D units; the adhesive monomer unit and the flexible monomer unit constitute a linear main chain, the substituent containing a catechol group contains a urea group, the catechol group is bonded to a silicon atom constituting the adhesive monomer unit via a urea bond containing the urea group, The flexible monomer unit is a dimethylsiloxane unit. Polysiloxane.

2. The flexible monomer unit accounts for 47 mol % or more and 95 mol % or less of the polysiloxane. The polysiloxane of claim 1.

3. The substituent containing a catechol group contains a hydrocarbon group. The polysiloxane of claim 1.

4. an adhesive monomer unit comprising an organosiloxane unit having a substituent that includes a modified catechol group having a silylated structure in which each hydrogen atom of two hydroxyl groups bonded to the ortho-position of a benzene ring is substituted with an alkylsilyl group; a flexible monomer unit comprising an organosiloxane unit that does not contain a catechol group or the modified catechol group; A polysiloxane which is a copolymer of both the adhesive monomer unit and the flexible monomer unit are D units; the adhesive monomer unit and the flexible monomer unit constitute a linear main chain, the substituent containing a modified catechol group contains a urea group, the modified catechol group is bonded to a silicon atom constituting the adhesive monomer unit via a urea bond containing the urea group; Polysiloxane.

5. The flexible monomer unit accounts for 47 mol % or more and 95 mol % or less of the polysiloxane. The polysiloxane of claim 4.

6. The substituent containing the modified catechol group contains a hydrocarbon group. The polysiloxane of claim 4.

7. Contains the polysiloxane according to any one of claims 1 to 6. glue.

8. A first polysiloxane and a second polysiloxane each comprising the polysiloxane according to any one of claims 1 to 6 and having a different content ratio of the flexible monomer unit from each other; An adhesive comprising:

9. A third polysiloxane comprising the polysiloxane according to any one of claims 1 to 6, wherein the content ratio of the flexible monomer unit in the third polysiloxane is different from that in the first polysiloxane and the second polysiloxane; The adhesive of claim 8 further comprising:

10. a precursor polysiloxane generating step for generating a precursor polysiloxane which is a copolymer of a first siloxane unit having a substituent containing a urea group and a second siloxane unit having a substituent consisting of a hydrocarbon group and not having a substituent containing a urea group, wherein both the first siloxane unit and the second siloxane unit are D units, and the first siloxane unit and the second siloxane unit constitute a linear main chain; a catechol group introduction step of reacting the precursor polysiloxane with a catecholamine to introduce a catechol group having two hydroxy groups bonded to the ortho positions of a benzene ring into the first siloxane unit via a urea bond containing the urea group; Including, The second siloxane unit is a dimethylsiloxane unit. A method for producing polysiloxane.

11. The precursor polysiloxane producing step comprises: a copolymerization step of forming a linear copolymer of a precursor first siloxane unit, which is a precursor of the first siloxane unit and has a compound containing an ammonium group as a substituent, and the second siloxane unit which does not have a compound containing an ammonium group as a substituent; a urea group forming step of reacting the copolymer formed in the copolymerization step with a carbonyl compound to replace the compound containing an ammonium group in the first precursor siloxane unit with the compound containing a urea group; The method for producing the polysiloxane according to claim 10, comprising:

12. A precursor polysiloxane generation process for generating a precursor polysiloxane which is a copolymer of a first siloxane unit having a substituent containing a urea group and a second siloxane unit having a substituent consisting of a hydrocarbon group and no substituent containing a urea group, wherein both the first siloxane unit and the second siloxane unit are D units, and a linear main chain is constituted by the first siloxane unit and the second siloxane unit; a catechol group introduction step of reacting the precursor polysiloxane with a catecholamine to introduce a catechol group having two hydroxy groups bonded to the ortho positions of a benzene ring into the first siloxane unit via a urea bond containing the urea group; an alkylsilyl group introducing step of reacting the polymer obtained in the catechol group introducing step with a silylating agent to substitute an alkylsilyl group for each hydrogen atom of the two hydroxy groups bonded to the ortho positions of the benzene ring; A method for producing a polysiloxane, comprising:

13. After the alkylsilyl group introduction step, an alkylsilyl group elimination step of replacing the alkylsilyl group with the hydrogen atom again to reform a structure in which two hydroxy groups are bonded to the ortho positions of the benzene ring; The method for producing the polysiloxane of claim 12, further comprising:

14. A preparation step of preparing a first polysiloxane and a second polysiloxane, each of which is obtained by the method for producing a polysiloxane according to any one of claims 10 to 13 and has a different content ratio of the second siloxane unit from each other; a mixing step of mixing the first polysiloxane and the second polysiloxane; A method for producing an adhesive comprising:

15. In the preparation step, at least a third polysiloxane is further prepared in addition to the first polysiloxane and the second polysiloxane, The third polysiloxane is obtained by the method for producing a polysiloxane according to any one of claims 10 to 13, and a content ratio of the second siloxane unit in the third polysiloxane is different from that of the first polysiloxane and the second polysiloxane, In the mixing step, in addition to the first polysiloxane and the second polysiloxane, at least the third polysiloxane is further mixed. A method for producing the adhesive according to claim 14.

Citation Information

Patent Citations

  • Organic silicon compound, adhesive composition, and article

    JP2015182978A

  • Modified polysiloxane and resin composition

    JP2021091820A

  • Ladder-like polysilsesquioxane, linear polysiloxane, adhesive, method for producing ladder-like polysilsesquioxane, and method for producing linear polysiloxane

    JP2021176953A

  • Catechol functional organopolysiloxane, method for producing the same and powder treatment agent

    JP2021187966A

  • Silicone pressure sensitive adhesive composition

    KR1020200134930A